Synthesis and anticancer activity of podophyllotoxin derivatives with nitrogen-containing heterocycles - Yin, Meng; Fang, Yongsheng; Sun, Xiaotong; Xue, Minggao; Zhang, Caimei; Zhu, Zhiyun; Meng, Yamiao; Kong, Lingmei; Myint, Yi Yi; Li, Yan; Zhao, Jingfeng; Yang, Xiaodong (Frontiers in Chemistry, 2023)
Three series of podophyllotoxin derivatives with various nitrogen-containing heterocycles were designed and synthesized. The antitumor activity of these podophyllotoxin derivatives was evaluated in vitro against a panel of human tumor cell lines. The results showed that podophyllotoxin-imidazolium salts and podophyllotoxin-1,2,4-triazolium salts a1–a20 exhibited excellent cytotoxic activity. Among them, a6 was the most potent cytotoxic compound with IC50 values of 0.04–0.29 μM. Podophyllotoxin-1,2,3-triazole derivatives b1–b5 displayed medium cytotoxic activity, and podophyllotoxin-amine compounds c1–c3 has good cytotoxic activity with IC50 value of 0.04–0.58 μM. Furthermore, cell cycle and apoptosis experiments of compound a6 were carried out and the results exhibited that a6 could induce G2/M cell cycle arrest and apoptosis in HCT-116 cells.